The mechanism of ω-assisted α phase formation in near β-Ti alloys. (15th July 2015) - Li, Tong; Kent, Damon; Sha, Gang; Dargusch, Matthew S.; Cairney, Julie M.
Graphical abstract: Abstract : Partitioning of alloying elements during the ω -to- α phase transformation in a near- β alloy after isothermal ageing at 573 K was measured using atom probe tomography and high-resolution transmission electron microscopy. O-rich regions associated with ω precipitates were observed for the first time, and likely serve as nucleation sites for the α phase. The partitioning behaviours of Al and O, unlike other elements, are different for α and ω, suggesting a mixed-mode mechanism for the ω -to- α phase transformation.